2022
DOI: 10.1002/csr.2376
|View full text |Cite
|
Sign up to set email alerts
|

Towards a sustainability management tool for food manufacturing small and medium‐sized enterprises—Insights from a Delphi study

Abstract: Small and medium-sized enterprises (SMEs) are crucial for a sustainable development of the food sector. Common tools to manage and improve business sustainability are not applied widely amongst food manufacturing SMEs yet. Therefore, this paper derives important aspects to consider for an SME-suitable tool, based on an extract from a Del-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…The Delphi method is centered on the superiority of group opinion over individual opinion (Kaplan et al, 1949). It is particularly beneficial for minimizing ambiguity and informing relevant and timely issues affecting organizations by using expert panels comprised of both practitioners and experts (Küchler et al, 2023;Worrell et al, 2013) and has shown to be a viable tool to investigate sustainable operations in developing countries (Ghag et al, 2023;Han et al, 2023). Delphi studies employ various panel sizes; the literature does not specify the number of experts required (Weidman et al, 2011), but a minimum of seven to eight participants is recommended, with some groups up to 60 participants (Geist, 2010;Shukor & Ng, 2022).…”
Section: Delphi Methodsmentioning
confidence: 99%
“…The Delphi method is centered on the superiority of group opinion over individual opinion (Kaplan et al, 1949). It is particularly beneficial for minimizing ambiguity and informing relevant and timely issues affecting organizations by using expert panels comprised of both practitioners and experts (Küchler et al, 2023;Worrell et al, 2013) and has shown to be a viable tool to investigate sustainable operations in developing countries (Ghag et al, 2023;Han et al, 2023). Delphi studies employ various panel sizes; the literature does not specify the number of experts required (Weidman et al, 2011), but a minimum of seven to eight participants is recommended, with some groups up to 60 participants (Geist, 2010;Shukor & Ng, 2022).…”
Section: Delphi Methodsmentioning
confidence: 99%